Implementasi Kurikulum Merdeka Untuk Meningkatkan Daya Berpikir Kritis Siswa Di Madrasah Aliyah Talippuki Kecamatan Mambi Kabupaten Mamasa - Hasbar (Publikasi dan UKI Toraja Press Universitas Kristen Indonesia Toraja, 2025)
Education is the main pillar for the progress of a country. Education is a basic element in improving human resources in developing and growing in each individual or the wider community. In line with the National Education System Law, Article 1 of 2003 states that education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have spiritual religious strength, self-control, personality, intelligence, noble morals, and skills needed for themselves, society, nation and st.